Test‐Retest Reliability of Pain Measures in Institutionalized Older Adults: Number of Painful Body Sites, Pain Intensity, and Pain Extent. Issue 3 (10th October 2020) - Silva, Anabela G.; De Francesco, Silvia; Rodrigues, Milton; Queirós, Alexandra; Cerqueira, Margarida
Abstract: Objective: The reliability of pain assessment in frail and older adults has seldom been assessed. This study aims to assess the test‐retest reliability of (1) the number of painful body sites, (2) pain intensity, and (3) pain extent in institutionalized older adults. Methods: Seventy‐four older adults who were institutionalized were assessed in 2 separate sessions, 2 days to 1 week apart, for pain intensity, number of painful body sites, and pain extent (in pixels) using a vertical pain numeric scale (0 to 10), a body chart divided into 50 body regions, and ImageJ, respectively. Intraclass correlation coefficients (ICCs), standard error of measurement (SEM), and minimal detectable differences (MDDs) were calculated. Results: In session 1, the mean values (± standard deviation) were 5.54 ± 2.12 points for pain intensity, 4.47 ± 3.27 for number of painful body sites, and 2, 726.00 ± 2, 322.09 for pain extent. ICCs were 0.82 (95% confidence interval [CI] = 0.72 to 0.89) for pain intensity, 0.89 (95% CI = 0.83 to 0.93) for number of painful body sites, and 0.74 (95% CI = −0.07 to 0.91) for pain area. The MDDs were 2.46 for pain intensity, 3.14 for number of painful body sites, and 4, 997.60 for pain extent. Conclusions: The vertical pain rating scale and the body chart seem reliable to assess pain intensity and number of pain sites, respectively. The wide CI for the ICC found for pain area and the high measurement error compromise its potential clinical relevance.